ADAPTATION OF DIGITAL BANKING CHANNELS BY INDIAN CONSUMERS- AN EMPIRICAL STUDY - Pallathadka, Harikumar; Kirana Pallathadka, Laxmi (International Journal of Psychosocial Rehabilitation, 2022)
Digital Banking facilities have a role to play in customer satisfaction as they are beneficial in providing services that are easy to use and cost-efficient at the same time. Digital banking has various channels to do their transactions (Mbama et al., 2018). The data collected through these channels help in formulating strategies by understanding the opportunities in the market. For the development of the economy, a banking system entailing the appropriate facilities is essential. The advent of IT has surfaced in all domains, including the banking sector. The advantages of internet banking services are innumerable. Hence, it has become imperative to study the connected matters of digital banking facilities. This study aims to propagate the understanding of consumers and their behavior about the digital banking channels and their adaptability in handling the technology. The paper deals with the individual factors linked to digital banking, such as privacy, ease of handling technology, security, and real-time access to data. A sample of 207 Indian consumers was surveyed to know the reason and level of adopting digital banking channels. The Chi-square test was applied to analyze the data and reach results. The study concludes that Indian consumers are showing a significant level of adoption of digital banking channels due to privacy, convenience, security, and 24X7 access.